A handbook on heat stress adaptation for women farmers - Macwan, N.; Maheriya, B.; Asodariya, G.; Joshi, A.; Kori, Pooja; Verma, Benu; Puskur, Ranjitha (2024)
Farmers—especially women—bear the brunt of climate-related challenges due to limited access to knowledge, resources, and support systems. Women’s social positioning, combined with the gendered division of labor, further exacerbates their vulnerability to climate change. In addition to farming responsibilities, women are often burdened with unpaid care work, increasing their workload and exposure to heat stress. This dual burden leaves them susceptible to the impacts of climate change, requiring targeted interventions that address both agricultural and social vulnerabilities. This handbook is designed to help women farmers comprehend how heat stress affects crop productivity, quality, and their overall wellbeing, while also offering actionable solutions to minimize its effects. Contributors: Nitin Macwan, Bhavna Maheriya, Gargi Asodariya, Aastha Joshi, Pooja Kori, Benu Verma, Ranjitha Puskur This handbook is available in English, Hindi, and Odiya languages.